The effects of subtitled videos on the listening comprehension of L2 learners in Bangladesh / Tasnim Haque Trisha - Tasnim, Haque Trisha (2018)
This study has analyzed the effects of different subtitled YouTube videos on the listening comprehension of L2 learners in Bangladesh including their auditory and visual learning style preferences. This study has employed the ‘post-test’ design and the ‘survey’ design in two phases. In the posttest design part, there are two experimental groups and one control group. The groups have received inputs of watching the same English video with English, Bengali, and no subtitles, respectively. After the inputs, they are given a 10-item multiple-choice questions test to test their listening comprehension following previous studies (Markham & Peter, 2003; Hayai & Mohmedi, 2011). In the survey design part, the groups are given a learning style preference questionnaire (adopted from Reid, 1995) which is consisted of 10 questions with a 5-point Likert scale on auditory and visual learning style preferences. The questionnaire is given to analyze the effects of these learning style preferences on listening comprehension. The participants of this study are 72 undergraduate low-proficiency level students (age group from 18 to 20) from a university in Bangladesh. The data of the ‘listening comprehension test’ is analyzed through a one-way ANOVA using the SPSS software and the data of ‘learning style preference’ survey is analyzed using the self-scoring sheet adopted from Reid (1995) and validated by the Learning style institute, C.I.T.E. The result of the ‘listening comprehension test’ shows that using bimodal subtitling in videos (L2 audio with L2 subtitles) helps learners perform better in listening comprehension compared to using L1 subtitles and no subtitles. The result of the ‘learning style preference’ survey shows that learners’ auditory and visual learning style preferences have effects on their listening comprehension but the effects are not significant.